2012
DOI: 10.1021/cm302015z
|View full text |Cite
|
Sign up to set email alerts
|

Length and Diameter Control of Ultrathin Nanowires of Substoichiometric Tungsten Oxide with Insights into the Growth Mechanism

Abstract: Tungsten oxide ultrathin nanowires have potential applications in electrochromic devices, dye sensitized solar cells, gas sensors, and as photocatalysts. Herein, we report a synthesis for solution phase ultrathin nanowires with independent control over the length and diameter. W(CO) 6 is used as the tungsten source, and the solvents octadecanol and octadecene are used. Morphological control is obtained by varying the ratios between these three components as well as reaction conditions such as time and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 58 publications
1
75
1
Order By: Relevance
“…[ 13 ] Mokari et al succeeded in obtaining freestanding ultrathin W 20 O 58 nanowires with controllable length and diameter, utilizing 1-octadecanol as the shape controlling agent and solvent and W(CO) 6 as the tungsten source. [ 14 ] Li et al controlled removal of surfactant from the presynthesized mesolamellar precursor and got W 18 O 49 nanowires with high aspect ratio. [ 15 ] Works mentioned above are nanorod or nanowire cases.…”
Section: Highly Flexible Sub-1 Nm Tungsten Oxide Nanobelts As Effi CImentioning
confidence: 99%
“…[ 13 ] Mokari et al succeeded in obtaining freestanding ultrathin W 20 O 58 nanowires with controllable length and diameter, utilizing 1-octadecanol as the shape controlling agent and solvent and W(CO) 6 as the tungsten source. [ 14 ] Li et al controlled removal of surfactant from the presynthesized mesolamellar precursor and got W 18 O 49 nanowires with high aspect ratio. [ 15 ] Works mentioned above are nanorod or nanowire cases.…”
Section: Highly Flexible Sub-1 Nm Tungsten Oxide Nanobelts As Effi CImentioning
confidence: 99%
“…[5 ] Copyright 2012 American Chemical Society. g-l) Growth kinetic of tungsten oxide nanowires: [ 10 ] g-i) TEM micrographs of aliquots obtained after 6 min (g), 10 min (h), and 14 min (i) scale bars are 50 nm; l) graph of the measured (black empty squares) average contour length of the nanowires as a function of reaction time, and the fi t of the data (red line) obtained by using the model described by Cademartiri et al [ 5 ] Adapted with permission. [ 10] Copyright 2013, American Chemical Society.…”
Section: Discussionmentioning
confidence: 99%
“…Anisotropic monomers are often invoked to justify the purely one-dimensional growth of nanowires. [ 10 ] …”
Section: Aggregation/coupling In Crystallization (Non-classical Crystmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent advances in the synthesis have made it possible to produce ultrathin (<10 nm) tungsten oxide nanowires with high aspect ratios. [19][20][21][22] It was shown that ultrathin tungsten oxide nanowires could be assembled into 2D thin films with tunable thickness over a very large area, exhibiting outstanding performance in gas sensing, in electrochromic devices and in photodetectors. [22][23][24] However, the assembly of these 1D nanostructures into 3D architectures remains an open task.…”
mentioning
confidence: 99%